Police Intelligence in Resolving Land Conflicts: Case Study of Land Conflict Resolution for the Construction of the Great Mosque in South Solok - Kukuh Wibowo; Arthur Josias Simon Runturambi; Achmad Sanusi (GoAcademica Research & Publishing, 2023)
Land conflict is something that is quite normal in Indonesia. In this case, land conflicts in the West Sumatra region occur quite often, because the existence of ulayat land is legally recognized by the state, and is included in Regional Regulations. The land conflict for the construction of the grand mosque in South Solok district has a complicated nature, where the problem which initially only involved the Regional Government and Kerinci Mitra Plantation widened to involve many parties including 2 (two) large mass organizations; to the indigenous people of the Rantau XII Koto Tribe Group who claim to have customary land in the area and make problems even more complicated which have the potential for horizontal conflict to emerge in the South Solok area. This research aims to see the role of police intelligence in resolving land conflicts with a case study of resolving land conflicts over the construction of a grand mosque in the South Solok district. The research method in this journal is a type of qualitative research that refers to a case study of land conflicts over the construction of the South Solok Grand Mosque. Interviews and document studies are used as data for analysis and decision-making. This research found that Police Intelligence has an important role in resolving conflicts in the context of maintaining security and order in society. In resolving land conflicts, police intelligence can act as a liaison between land owners, local communities, legal authorities, and other related parties. By facilitating dialogue, negotiation, or mediation, police intelligence can help reach a solution that is acceptable to all parties involved (win-win solution).